EFEKTIVITAS PENGGUNAAN MEDIA FILM KARTUN BAHASA ARAB DALAM MENINGKATKAN MAHARAH ISTIMA’ SANTRI AQOBAH - Lailatul maghviroh; muhammad arif setyabudi (JURNAL AL-IHDA' : Media Ilmiah Bahasa Arab, 2025)
Arabic is a very important foreign language because it is the main key in understanding Islamic texts such as the Qur'an and Sunnah. In today's technological development, digital media plays an important role in the world of education, including in language learning. One form of interesting media is audiovisual multimedia such as animated videos and cartoon films, which not only help understanding but also increase learning motivation. This study aims to determine the effectiveness of using Arabic cartoon film media in improving listening skills (maharah istima') of students at Pondok Pesantren Aqobah Jombang. This study uses a quantitative approach with a quasi-experimental design through pretest and posttest on 29 students of the Arabic Night program. Data analysis was conducted using SPSS 16 with normality test, paired t-test, and N-Gain analysis. The results showed an increase in the mean score from 69.31 (pretest) to 83.79 (posttest), with a significance of 0.000 <0.05. The N-Gain value of 0.5034 or 50.34% is categorized as quite effective.Arabic cartoon film media proved effective in improving listening skills because it presents language in an interesting visual and auditory context and in accordance with the character of adolescents. This media can be an innovative learning alternative in the pesantren environment.